Central nesfatin‐1 influences the excitability of ghrelin‐responsive gastric distension neurons in the arcuate nucleus and reduces gastric motility in rats. Issue 11 (23rd September 2013) - Li, Zhi‐ling; Xu, Luo; Sun, Xiang‐rong; Guo, Fei‐fei; Gong, Yan‐ling; Gao, Sheng‐li
Abstract Although the novel satiety peptide nesfatin‐1 has been shown to regulate gastric motility, the underlying mechanisms have yet to be elucidated. The study aimed to explore the effects of nesfatin‐1 on ghrelin‐responsive gastric distension (GD) neurons in the arcuate nucleus (Arc), and potential regulation mechanisms of gastric motility by the paraventricular nucleus (PVN). Single‐unit discharges in the Arc were recorded extracellularly, and gastric motility in conscious rats was monitored during the administration of nesfatin‐1 to the Arc or electrical stimulation of the PVN. Retrograde tracing and fluo‐immunohistochemistry staining were used to determine NUCB2/nesfatin‐1 neuronal projections. Nesfatin‐1 inhibited most of the ghrelin‐responsive GD‐excitatory neurons, but excited ghrelin‐responsive GD‐inhibitory neurons in the Arc. Gastric motility was significantly reduced by nesfatin‐1 administration to the Arc in a dose‐dependent manner. The firing activity in the Arc and changes to gastric motility were partly reduced by SHU9119, an antagonist of melanocortin 3/4 receptors. Electrical stimulation of PVN excited most of the ghrelin‐responsive GD neurons in the Arc and promoted gastric motility. Nonetheless, pretreatment with an anti‐NUCB2/nesfatin‐1 antibody in the Arc further increased the firing rate of most of the ghrelin‐responsive GD‐excitatory neurons and decreased the ghrelin‐responsive GD‐inhibitory neurons following electrical stimulation of the PVN. Gastric motility was enhanced by pretreatment with an anti‐NUCB2/nesfatin‐1 antibody in the Arc following PVN stimulation. Furthermore, NUCB2/nesfatin‐1/fluorogold double‐labeled neurons were detected in the PVN. These results suggest that nesfatin‐1 could serve as an inhibitory factor in the Arc to regulate gastric motility via the melanocortin pathway. The PVN could be involved in the regulation of the Arc in gastric activity.